Environmental Benefit and Investment Value of Hydrogen-Based Wind-Energy Storage System - Xue, Qing; Wang, Zhen; Zhang, Yuqing (Frontiers in Energy Research, 2021)
Alongside the rapid expansion of wind power installation in China, wind curtailment is also mounting rapidly due to China's energy endowment imbalance. The hydrogen-based wind-energy storage system becomes an alternative to solve the puzzle of wind power surplus. This paper introduced China's energy storage industry's development and summarized the advantages of hydrogen-based wind-energy storage systems. From the perspective of resource conservation, it estimated the environmental benefits of hydrogen-based wind-energy storages. This paper also builds a valuation model based on the Real Options Theory to capture the distinctive flexible charging and discharging features of the hydrogen-based wind-energy storage systems. Based on the model, simulation results, including the investment value and operation decision of the hydrogen energy storage system with different electricity prices, system parameters, and different levels of subsidies, are presented. The results show that the hydrogen storage system fed with the surplus wind power can annually save approximately 2.19 3.29 million tons of standard coal consumption. It will reduce 3.31 4.97 million tons of CO2, SO2, NOx, and PM, saving as much as 286.6 429.8 million yuan of environmental cost annually on average. The hydrogen-based wind-energy storage system's value depends on the construction investment and operating costs and is also affected by the mean-reverting nature and jumps or spikes in electricity prices. The market-oriented reform of China's power sector is conducive to improving hydrogen-based wind-energy storage systems' profitability. At present, subsidies are still essential to reduce initial investment and attracting enterprises to participate in hydrogen energy storage projects.